Research on Student Satisfaction with the Quality of Training Services at Vietnam National University of Agriculture - Thi Minh Hue, Nguyen; Thi Kim Oanh, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 42 No 1DO - 10.25073/2588-1116/vnupam.4582, 2026)
Abstract: This study aims to assess the satisfaction of students with the quality of training services at Vietnam National University of Agriculture used the descriptive statistical analysis, the reliability testing of measurement scales (Cronbach’s Alpha), and multiple regression analysis through data from 1,931 graduates from the academic year 2023-2024. The findings reveal five factors affecting student satisfaction, including student support services, facilities, lecturers, training management, and curriculum; in which, the strongest influence is the student support services factor. The study suggests that the University should prioritize improving student support services, investing in infrastructure and learning facilities, and continuously innovating the curriculum in order to enhance student satisfaction and the overall quality of educational services. Keywords: Student satisfaction, Training services quality , Vietnam National University of Agriculture.